Systematic Review: The Impact of Antimicrobial Stewardship Program Implementation in Hospital Intensive Care Units - Tifany Maulida Candra; Nadia Farhanah Syafhan; Fransisca Dhani Kurniasih (Green Publisher Indonesia, 2024)
Antimicrobial resistance represents a significant challenge in clinical settings, particularly in intensive care units (ICUs). The incidence of antimicrobial resistance in the ICUs has reached 30% of all hospital patients. Furthermore, over 71% of patients on the unit were using antibiotics. Consequently, infections contribute substantially to the elevated mortality and morbidity rates in patients with critical status. The Antimicrobial Stewardship Program (ASP) is a program that refers to a multidisciplinary approach to optimize the appropriate use of antimicrobials. This systematic review aims to identify ASP policies implemented in hospital ICUs, utilizing various parameters for assessment. This systematic review was conducted using PubMed, Scopus, Google Scholar, and the Cochrane Database of Systematic Reviews, focusing on publications from January 1, 2015, to June 1, 2024. A comprehensive review of 4,419 articles identified 12 studies that met the inclusion and exclusion criteria. The primary goal of ASP is to enhance the appropriateness of antimicrobial use, ensuring accurate prescribing practices in terms of indication, antimicrobial selection, route of administration, and therapy duration. The outcomes of ASP implementation are evaluated based on decreased in antimicrobial use, increased in the number of recommendations, decreased in treatment costs, and a decrease in multidrug-resistant organism (MDRO) incidence. Although numerous articles have provided positive results regarding the implementation of ASP in ICU settings, there remains a need for extensive and structured research to validate these findings comprehensively.